1761 Temp. Acts and Laws of His Majesty's Province of New-Hampshire in New-England, at 1-2 - (:unkn) unknown (General Publisher, 1759)
And every justice of the peace within this province, may cause to be stayed and arrested, all affrayers, rioters, disturbers or breakers of the peace, or any other who shall go armed offensively, or put his Majesty's subjects in fear, by menaces or threatening speeches
--
Keywords: GOING ARMED